Benign ethnic neutropenia in a South African population, and its association with HIV acquisition and adverse event reporting in an HIV vaccine clinical trial - Mpofu, Rephaim (PLoS One, 2021)
Benign ethnic neutropenia (BEN) is defined as a neutrophil count of <1.5×10(9) cells/L in healthy individuals and is more common in populations of certain ethnicities, e.g. African or Middle Eastern ethnicity. Neutrophil values are commonly included in eligibility criteria for research participation, but little is known about the relationship between BEN, HIV acquisition, and the occurrence of adverse events during clinical trials. We investigated these relationships using data from an HIV vaccine efficacy trial of healthy adults from 5 South African sites. We analysed data from the double-blind, placebo-controlled, randomized trial HVTN 503, and its follow-on study HVTN 503-S to assess the prevalence of BEN, its association with HIV infection, and adverse event reporting. These data were then compared with a time- and age-matched, non-pregnant cohort from the National Health and Nutrition Examination Survey (NHANES) conducted between 2007–2008 in the United States (US). The 739 South African participants had a median age of 22.0 years (interquartile range = 20–26) and 56% (n = 412) were male. Amongst the US cohort of 845 participants, the median age was 26 (IQR: 21–30) and the majority (54%, 457/745) were also male. BEN was present at enrolment in 7.0% (n = 52) of South African participants (6% in the placebo group versus 8% in the vaccine group); 81% (n = 42) of those with BEN were male. Pretoria North had the highest prevalence of BEN (11.6%, 5/43), while Cape Town had the lowest (0.7%, 1/152). Participants with BEN had a lower median neutrophil count (1.3 vs. 3.2x10(9) cells/L; p<0.001) and BMI (20.8 vs. 22.3 kg/m(2); p<0.001) when compared to those without BEN. A greater proportion of Black South Africans had neutrophil counts <1.5×10(9) cells/L compared to US non-Hispanic Whites from the NHANES cohort (7% [52/739] vs. 0.6% [3/540]; p<0.001). BEN did not increase the odds for HIV infection (adjusted odds ratio [aOR]: 1.364, 95% confidence interval [95% CI]: 0.625–2.976; p = 0.4351). However, female gender (aOR: 1.947, 95% CI: 1.265–2.996; p = 0.0025) and cannabis use (aOR: 2.192, 95% CI: 1.126–4.266; p = 0.0209) increased the odds of HIV acquisition. The incidence rates of adverse events were similar between participants in the placebo group with BEN, and those without: 12.1 (95% CI: 7.3–20.1) vs. 16.5 (95% CI: 14.6–18.7; p = 0.06) events per 100 person-years (py) were noted in the infections and infestations system organ class, respectively. The vaccine group had an event incidence rate of 19.7 (95% CI: 13.3–29.2) vs. 14.8 (95% CI: 13.0–16.8; p = 0.07) events per 100py in the group with, and without BEN, respectively. BEN is more prevalent in Black South Africans compared to US Non-Hispanic Whites. Our data do not support excluding populations from HIV vaccine trials because of BEN. BEN was not associated with increased risk for HIV infection or Adverse events on a vaccine trial. Predictors of HIV infection risk were females and cannabis use, underlying the continued importance of prevention programmes in focusing on these populations.